2015
DOI: 10.1101/gr.187823.114
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of post-zygotic structural genetic aberrations in the cells of histologically normal breast tissue that can predispose to sporadic breast cancer

Abstract: Sporadic breast cancer (SBC) is a common disease without robust means of early risk prediction in the population. We studied 282 females with SBC, focusing on copy number aberrations in cancer-free breast tissue (uninvolved margin, UM) outside the primary tumor (PT). In total, 1162 UMs (1–14 per breast) were studied. Comparative analysis between UM(s), PT(s), and blood/skin from the same patient as a control is the core of the study design. We identified 108 patients with at least one aberrant UM, representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(71 reference statements)
2
29
1
Order By: Relevance
“…Interestingly, the duplicated haploid copy of chr1q in BN-T was not identical to that observed in the breast cancer samples ( Figure 3B). Although another study observed that oncogene amplification was a major factor in clonal expansion of premalignant cells (23) in the breast, this seems not to be the trigger event of premalignant cells in our study, but suggests that point mutations might be drivers of clonal expansion of premalignant cells.…”
Section: Sequencing Of Single Cells and Cell Pools Identified The Evomentioning
confidence: 54%
“…Interestingly, the duplicated haploid copy of chr1q in BN-T was not identical to that observed in the breast cancer samples ( Figure 3B). Although another study observed that oncogene amplification was a major factor in clonal expansion of premalignant cells (23) in the breast, this seems not to be the trigger event of premalignant cells in our study, but suggests that point mutations might be drivers of clonal expansion of premalignant cells.…”
Section: Sequencing Of Single Cells and Cell Pools Identified The Evomentioning
confidence: 54%
“…Recently, Forsberg et al used whole genome analysis of breast cancer and adjacent histologically normal tissues (uninvolved margins at varying distances) to demonstrate that the most common genomic abnormality in adjacent normal tissue was a gain in gene copy number of ERBB2. Following ERBB2 genomic amplification, amplification of other growth factor receptor genes (EGFR, FGFR1, IGF1R, LIFR, and NGFR) were the most frequent genetic aberrations [52]. The above studies provide compelling evidence that the presence of genomic instability and specific cancer-related chromosomal aberrations are often present in histologically normal tissue adjacent to breast tumors.…”
Section: Cancer-like Alterations In Tumor Adjacent Histologically Normentioning
confidence: 99%
“…For example, sequencing data from a large-scale case-control study suggests mosaic protein truncating mutations in PPM1D may be a risk factor for breast and ovarian cancer[58], although further prospective studies are needed to verify this relationship. Additionally, a recent investigation of uninvolved margin tissue from breast cancer cases suggests mosaic copy number aberrations are present in over a third of cases and often include mosaic gains of ERBB2 and growth factor receptor genes[59]. Better understanding which events are important for future disease risk and the penetrance of such events will be important as the field moves forward in assessing clonal mosaicism as markers of risk for common diseases.…”
Section: Detection Of Genetic Mosaicism As a Biomarkermentioning
confidence: 99%